The Innovation of Virtual Tour of Malang State University Learning Museum as an Alternative for Educational Tourism in the Disruptive Era - Nafi'ah, Ulfatun; Sapto, Ari; Sayono, Joko; Herdiyani, Aulia; Smith, George (KnE Social Sciences, 2023)
Advances in technology and information have become a stimulus for life changes, including digitalization and the internet of things. These two things linearly then motivate researchers to present an innovation virtual museum tour. The aim of the researcher is to present this innovation to assist in the process of developing educational tourism in Indonesia, especially for the UM Learning Museum. In addition, this innovation is also carried out with the aim of bringing the museum closer as one of the media for inheriting culture to the community through the help of advances in technology and information. The virtual tour innovation is also carried out with the aim of stimulating the development of innovation through enriching essence and behavioral intention. In order to facilitate efforts to achieve these goals, the research and development method from Borg and Gall has been modified. Through this method, it was found that the virtual tour innovation of the UM Learning Museum has many benefits for visitors, such as the experience of exploring independently and interactively. Other benefits obtained from the virtual tour of the UM Learning Museum include getting new information and knowledge and developing behavioral intentions to support the existence of the UM Learning Museum for the community. Keywords: learning media, innovation, virtual tour, UM Learning Museum